Honey bee introductions displace native bees and decrease pollination of a native wildflower. Issue 2 (3rd January 2023) - Page, Maureen L.; Williams, Neal M.
Abstract: Introduced species can have cascading effects on ecological communities, but indirect effects of species introductions are rarely the focus of ecological studies. For example, managed honey bees ( Apis mellifera ) have been widely introduced outside their native range and are increasingly dominant floral visitors. Multiple studies have documented how honey bees impact native bee communities through floral resource competition, but few have quantified how these competitive interactions indirectly affect pollination and plant reproduction. Such indirect effects are hard to detect because honey bees are themselves pollinators and may directly impact pollination through their own floral visits. The potentially huge but poorly understood impacts that non‐native honey bees have on native plant populations combined with increased pressure from beekeepers to place hives in U.S. National Parks and Forests makes exploring impacts of honey bee introductions on native plant pollination of pressing concern. In this study, we used experimental hive additions, field observations, as well as single‐visit and multiple‐visit pollination effectiveness trials across multiple years to untangle the direct and indirect impacts of increasing honey bee abundance on the pollination of an ecologically important wildflower, Camassia quamash . We found compelling evidence that honey bee introductions indirectly decrease pollination by reducing nectar and pollen availability and competitively excluding visits from more effective native bees. In contrast, the direct impact of honey bee visits on pollination was negligible, and, if anything, negative. Honey bees were ineffective pollinators, and increasing visit quantity could not compensate for inferior visit quality. Indeed, although the effect was not statistically significant, increased honey bee visits had a marginally negative impact on seed production. Thus, honey bee introductions may erode longstanding plant‐pollinator mutualisms, with negative consequences for plant reproduction. Our study calls for a more thorough understanding of the indirect effects of species introductions and more careful coordination of hive placements.